Exploring cyclodextrin-driven advancements in aqueous Zn-ion battery: A review - Ahmed Hazem Abdelhay (20487281) (2024)
The growing demand for sustainable and efficient energy storage solutions has emphasized the value of aqueous zinc-ion batteries (AZIBs) as a safer and less expensive alternative to lithium-ion batteries. Despite their potential, AZIBs confront considerable obstacles, particularly the production of zinc dendrites and side reactions such hydrogen evolution, which limit their cycling stability and practical applicability. In this review, we explore the prospective function of cyclodextrins (CDs), a type of supramolecular carbohydrate polymer, in addressing such challenges. CDs, with their unique capacity to form inclusion complexes, provide an innovative approach for controlling zinc deposition, limiting dendrite development, and minimizing parasitic interactions. We present a detailed assessment of recent improvements in the use of CDs to change electrolytes and the electrode/electrolyte interface, resulting in improved electrochemical performance of AZIBs. This review focuses on CDs' potential as multifunctional additives for improving zinc anode stability, extending battery life, and facilitating large-scale AZIB adoption. Other Information Published in: Carbohydrate Polymers License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.carbpol.2024.123041